PAI SD Test Quality Analysis: Validity and Reliability Review - Pipit Pitriani; Enung Nugraha; Fitri Hilmiyanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the quality standards of test instruments, namely the difficulty level index, discrimination index, validity and reliability of the PAI UAS test made by PAI teachers in Tigaraksa District. This study is a descriptive study with a qualitative and quantitative approach. Data was taken using documentation data, namely PAI UAS question documents student test results. Qualitative data was analyzed logically using Bloom's Taxonomy theory. Quantitative data was analyzed to calculate the difficulty level index, the discrimination index, the validity test used the point biserial correlation technique and the validity test used the Kuder Richadson 20 (KR-20) correlation technique. The study results showed that 47.5% of the questions were at cognitive level C1. In general, the PAI test items developed by PAI teachers in Tigaraksa District, the quality of the Islamic Religious Education (PAI) questions produced is still far from standard. This is based on the fact that there are still many invalid items and the reliability index of the test instrument is categorized as unreliable.